Crop sequence and P fertilization effects on soil P fractions under no-tillage - Appelhans, Stefania Carolina; Novelli, Leonardo Esteban; Melchiori, Ricardo Jose; Gutierrez Boem, Flavio Hernán; Caviglia, Octavio (Springer, 2021)
Increasing cropping intensity may affect phosphorus (P) recycling through crop residue inputs, which may differ in soils with different productivity, P adsorption capacity, and P fertilization level. In three crop sequences: Soybean (Glycine max L. Merr.) monoculture (S–S), Maize (Zea mays L.) monoculture (M-M), and Wheat (Triticum aestivum L.)/Soybean as a double crop (W/S) in a Vertisol and a Mollisol; we assessed the long-term effect of the crop sequences on soil inorganic P (Pi) and organic P (Po) fractions, and the short-term effect of P fertilization on soil Pi and Po fractions, P uptake, and grain yield. Two P fertilization levels (50 kg P ha−1, and control) were established in 2016 on long-term experiments that included S–S, W/S, and M-M. Bray1-P, as well as total P, Po, and Pi in both the coarse soil (> 53 μm) fraction (CF) and the NaHCO3 extract, and accumulated yield and P uptake were measured. In the long-term, the crop sequences did not change soil P fractions, but Po-CF and Pi-CF showed similar values in both soils, suggesting less soil-type dependence than in other labile P fractions. In the short-term, the P fertilization only increased the extractable Pi fractions (16% in the Mollisol and 25% in the Vertisol), suggesting that P in the CF was not a sink of P fertilizer. Our study showed that P fertilization in different crop sequences may increase labile P fractions and P recycling depending on soil type, a useful tool to develop P fertilization strategies at the crop sequence level.